The Antagonistic Effect of Mycotoxins Deoxynivalenol and Zearalenone on Metabolic Profiling in Serum and Liver of Mice - Ji, Jian; Zhu, Pei; Cui, Fangchao; Pi, Fuwei; Zhang, Yinzhi; Li, Yun; Wang, Jiasheng; Sun, Xiulan (Toxins, 2017)
Metabolic profiling in liver and serum of mice was studied for the combined toxic effects of deoxynivalenol (DON) and zearalenone (ZEN), through gas chromatography mass spectrum. The spectrum of serum and liver sample of mice, treated with individual 2 mg/kg DON, 20 mg/kg ZEN, and the combined DON + ZEN with final concentration 2 mg/kg DON and 20 mg/kg ZEN for 21 days, were deconvoluted, aligned and identified with MS DIAL. The data matrix was processed with univariate analysis and multivariate analysis for selection of metabolites with variable importance for the projection (VIP) > 1, t-test p value < 0.05. The metabolic pathway analysis was performed with MetaMapp and drawn by CytoScape. Results show that the combined DON and ZEN treatment has an obvious “antagonistic effect” in serum and liver tissue metabolic profiling of mice. The blood biochemical indexes, like alkaline phosphatase, alanine transaminase, and albumin (ALB)/globulin (GLO), reveal a moderated trend in the combined DON + ZEN treatment group, which is consistent with histopathological examination. The metabolic pathway analysis demonstrated that the combined DON and ZEN treatment could down-regulate the valine, leucine and isoleucine biosynthesis, glycine, serine and threonine metabolism, and O-glycosyl compounds related glucose metabolism in liver tissue. The metabolic profiling in serum confirmed the finding that the combined DON and ZEN treatment has an “antagonistic effect” on liver metabolism of mice.